The Effect of Partlect Exercise and Circuit Training on VO2Max of Basketball Extracurricular Students at SMA Negeri 1 Lahat - Putra, Ardiansyah; Manullang, Jujur Gunawan; Imansyah, Farizal (Journal of Social Work and Science Education, 2023)
This research is quantitative with the type of experimental design. This study aims to determine 1) the effect of fartlek training on increasing the vo2max ability of basketball extracurricular students at SMA Negeri 1 Lahat, 2) the effect of circuit training on increasing the vo2max ability of basketball extracurricular students at SMA Negeri 1 Lahat, 3) differences in the effect of fartlek and circuit training on increasing the vo2max ability of basketball extracurricular students at SMA Negeri 1 Lahat. The sample in this study were 30 students who took part in basketball extracurricular activities at SMA Negeri 1 Lahat. The data analysis technique used the T test. The prerequisite test for data analysis used the normality test with the Lilliefors test with α = 0.05 and the homogeneity test of variance with the Barlet test α = 0.05. The results of the study 1. There is a significant effect of Fartlek training on the vo2max ability of basketball extracurricular students at SMA Negeri 1 Lahat, 2. There is a significant effect of Circuit Training on the vo2max ability of basketball extracurricular students at SMA Negeri 1 Lahat, 3. There is a significant difference in Fartlek training and circuit training exercises.